Identification of Major Sequence Types among Multidrug-Resistant Staphylococcus epidermidis Strains Isolated from Infected Eyes and Healthy Conjunctiva - Jena, Smrutiti; Panda, Sasmita; Nayak, Kinshuk C.; Singh, Durg V. (Frontiers in Microbiology, 2017)
We examined the presence of virulence and antibiotic resistance genes, SCCmec types and determined the genomic diversity among ocular S. epidermidis isolates (patients-23, healthy controls-29). PCR determined the presence of antibiotic resistance genes, virulence genes and SCCmec types among all isolates. MLST and PFGE determined the genomic relatedness among them. All isolates of S. epidermidis showed resistance to at least one class of antibiotics of which 48 isolates were multidrug resistant and carried ARGs. Thirty-five isolates were methicillin resistant and carried mecA gene. Majority of the isolates were resistant to fluoroquinolones and showed mutation in gyrA, parC and parE genes, however, few isolates showed additional novel mutations in parC gene. Of the MRSE strains, 17 strains carried SCCmec type IV, four type V, two type II, and two UT4. Seven strains carried novel combination of ccr complex and SCCmercury element, not reported earlier. All the S. epidermidis strains harboured icaA and icaD genes, 47 carried ACME operon, and 50 contained IS256. A noteworthy finding was the presence of ST179 among 43% of infected eye isolates an observation rarely reported among S. epidermidis. PFGE and MLST analysis showed genomic diversity among them. Statistical analysis suggests that few healthy conjunctiva isolates had characteristics similar to infected eye isolates. S. epidermidis strains carrying mecA gene are multidrug resistant, virulent and diverse irrespective of sources of isolation. IS256 cannot be used as marker to differentiate isolates of infected eye from healthy conjunctiva.